(untitled) (Acta Entomológica Chilena, 2022)
Scytodes globula is a common arachnid that inhabits homes in central Chile. The genus is well known as spitting spiders, because of their ability for using a sticky saliva to catch their preys. This behavior exhibited by Scytodes is part of a complex feeding pattem, which enables them to feed on a wide range of preys, such as Loxosceles laeta, one of the most dangerous spiders for humans. In this article the predatory and reproductive behaviour of Scytodes globula and its life cycle are studied and described under laboratory condition